7. Usefulness of Low-Intensity Pulsed Ultrasound (LIPUS) for the Treatment of Osteochondritis Dissecans (OCD) of the Humeral Capitellum. Issue 8 (August 2016) - Kusano, Hiroshi; Furushima, Kozo; Mitsui, Yasuhiro; Miyamoto, Azusa; Urata, Daigo; Serita, Yu; Itoh, Yoshiyasu
Abstract : Objectives: LIPUS has been reported to promote bone union in pseudoarthrosis and delayed fracture union as well as to have a beneficial effect in shortening the duration of bone healing in fresh fractures. The purpose of this study was to examine whether LIPUS has an accelerating effect on healing OCD. Subjects and Methods: From 2008 to 2012, cases with advanced-stage OCD were randomized, and the study was conducted on 51 patients (LIPUS group) who enabled us to decide the treatment efficacy, and gave consent after receiving an explanation on the benefit of LIPUS. LIPUS was performed for 20 minutes every day by treating the elbow in 2 directions, namely on the external and internal sides. The patients were told to stop pitching and batting. Plain radiography was performed once every 6 weeks and computed tomography (CT) scans were performed approximately once every 3 months. Image repair criteria were that the outside localized type was repaired completely, and the central localized or extensive type had lesion occupancy of less than 20%. Twenty-nine of 51 who did not recover and received surgical operation were excluded in the study, and 22 patients who were healed with LIPUS were compared with 21 patients who received conservative therapy only. Results and Discussion: The image repair period for the LIPUS group was an average of 4.5 ± 1.9 months, while for the non-LIPUS group it was 6.8 ± 3.8 months. LIPUS treatment for OCD significantly shortened the image repair period ( P = 0.037). It is necessary to increase the number of cases, and clarify the utility of LIPUS.